Association between physician specialty and risk of prescribing inappropriate pill splitting. - Chia-Yu Chou; Chia-Chen Hsu; Shu-Chiung Chiang; Chin-Chin Ho; Chia-Lin Chou; Min-Shan Wu; Yuh-Lih Chang; Han-Yi Tsai; Tzeng-Ji Chen; Yueh-Ching Chou (PLoS ONE, 2013)
BACKGROUND: Prescription errors that occur due to the process of pill splitting are a common medication problem; however, available prescription information involving inappropriate pill splitting and its associated factors is lacking. METHODS: We retrospectively evaluated a cohort of ambulatory prescriptions involving extended-release or enteric-coated formulations in a Taiwan medical center during a 5-month period in 2010. For this study, those pill splitting prescriptions involving special oral formulations were defined as inappropriate prescriptions. Information obtained included patient demographics, prescriber specialty and prescription details, which were assessed to identify factors associated with inappropriate pill splitting. RESULTS: There were 1,252 inappropriate prescriptions identified in this cohort study, representing a prescription frequency for inappropriate pill splitting of 1.0% among 124,300 prescriptions with special oral formulations. Among 35 drugs with special oral formulations in our study, 20 different drugs (57.1%, 20/35) had ever been prescribed to split. Anti-diabetic agents, cardiovascular agents and central nervous system agents were the most common drug classes involved in inappropriate splitting. The rate of inappropriate pill splitting was higher in older (over 65 years of age) patients (1.1%, 832/75,387). Eighty-seven percent (1089/1252) of inappropriate prescriptions were prescribed by internists. The rate of inappropriate pill splitting was highest from endocrinologists (3.4%, 429/12,477), nephrologists (1.3%, 81/6,028) and cardiologists (1.3%, 297/23,531). Multivariate logistic regression analysis revealed that the strongest factor associated with individual specific drug of inappropriate splitting was particular physician specialties. CONCLUSION: This study provides important insights into the inappropriate prescription of special oral formulation related to pill splitting, and helps to aggregate information that can assist medical professionals in creating processes for reducing inappropriate pill splitting in the future.